KUALITAS PELAYANAN PEMBUATAN PASPOR PADA KANTOR IMIGRASI KELAS I PEKANBARU - Rina Pahlawati; Sujianto, " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes about the service quality in passport at Immigration Office Class I Pekanbaru. While the background of this research is not only Immigration Office as the place to serve public in passport, but also the persistence of public complaints related to the passport. This research is based on the interviews and observations as initial data of the writer who found that there are indications of problems such social inequalities associated kinship/relationship, diverse completion time of passport, and existing facilities at the Immigration Office Pekanbaru Class I still yet support in the continuity of passport service. The purpose of this research was to determine the analysis of service quality in passport at the Immigration Office Class I Pekanbaru.The writer used the theory of Agus Dwiyanto which consists of 5 dimensions namely, dimension of officer attitudes, procedures, time, facilities and service charges. The method used is descriptive analysis with data collection through library research and field studies (observations and interviews).Therefore, the conclusion of this research is service quality in passport at the Immigration Office Class I Pekanbaru based on each dimension, dimension of officer attitudes is not quite good, dimension of procedure is good, dimension of time has a different opinion depends on completion time of passport, facilities are quite good, service charge is not quite optimal related to information costs, so that the overall quality of service passport at the Immigration Office Class I Pekanbaru is good enough. Only Immigration Office Class I Pekanbaru to further improve the performance of services so that services are provided to the people who will make the passport can run optimally.Keywords : Quality, Service, Passport, Immigration Office, Pekanbaru